Pengaruh Model Pembelajaran Kaffah terhadap Karakter dan Kemampuan Pemecahan Masalah Peserta Didik pada Materi Momentum dan Impuls - Solihin Rahmat; Syahrial Ayub; Ni Nyoman Sri Putu Verawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze the effect of the Kaffah Learning Model on students’ character development and problem-solving abilities in the topic of momentum and impulse. The study employed a quasi-experimental method using a nonequivalent control group design. The research subjects were Grade XI students consisting of an experimental class and a control class. Data were collected through a problem-solving ability test and a student character questionnaire. Data analysis was conducted using normality tests, Levene’s test and Box’s M test for homogeneity, and hypothesis testing through Multivariate Analysis of Variance (MANOVA). The results showed that the Kaffah Learning Model had a significant effect on both problem-solving abilities and character development simultaneously. Students who participated in learning activities using the Kaffah Learning Model demonstrated better character development and higher problem-solving abilities compared to those who received conventional instruction. Therefore, the Kaffah Learning Model can be considered an effective alternative instructional model for enhancing students’ character and problem-solving abilities in physics learning.